The Melville singer - Tsumele, Edward (Rhodes University, 2026)
My thesis comprises a collection of short stories. I explore how the intersection of race and class, concepts that often have negative connotations in society, can be used in fiction to sustain a narrative, at times with the use of humour. Using the motif of race and/or class, I seek to demonstrate how these concepts can be harnessed to exploit the attitudes, prejudices and complexities of characters that come from different cultural backgrounds to sustain the narrative voice. My thesis is influenced by the ways in which Chris Abani depicts place in his short stories, with his short stories placing a reader to place, feeling its energy and smell and visualising it, and Ayi Kwei Armah’s ability to breathe life into the mundane by writing about objects as if they are living things. Structurally, I follow Joseph Campbell’s study of narrative conventions in A Hero with a Thousand Faces, discarding the conventions when appropriate. This technique assists me in drawing the reader into the story, almost as a participant in its making by leaving them in suspense and asking questions about the motives and action of the protagonists. Niq Mhlongo’s short story anthology For You I’d Steal a Goat (Kwela Books, 2022), and Siphiwo Mahala’s African Delights (Jacana, 2011) have inspired me to adopt both the very short and short story form.
Keywords: Uncatalogued